Chiari-like displacement due to spontaneous intracranial hypotension in an adolescent: successful treatment by epidural blood patch - Schönberger, Jan; Möhlenbruch, Markus Alfred; Seitz, Angelika; Bußmann, Cornelia; Bächli, Heidi; Kölker, Stefan (European journal of paediatric neurology, 2017)
Background: Spontaneous intracranial hypotension is a rarely diagnosed cause of headache, especially in children and adolescents. It is due to cerebrospinal fluid (CSF) leakage via spinal fistulae occurring without major trauma. Case presentation: An adolescent patient presented with a 3-month history of strictly postural headache. Cranial magnetic resonance imaging (MRI) showed pronounced Chiari-like prolapse of the cerebellar tonsils, narrow ventricles and enlarged cerebral veins. On spinal MRI, myelographic sequences revealed a large collection of CSF around the first sacral roots. CT myelography proved extensive spinal CSF leakage. Hence, we applied epidural patches at multiple levels. Afterwards, symptoms and radiologic findings, including Chiari-like displacement, completely resolved. Conclusion: A Chiari-like descent of the cerebellar tonsils alone does not secure the diagnosis of a Chiari I malformation. Especially if other findings indicate spinal CSF leakage, a systematic work-up should be initiated. In most cases, interventional techniques seal the leak successfully, resulting in a favorable outcome.